2019
DOI: 10.1007/s10637-019-00838-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cellular effects of novel 1,3,5-triazine derivatives in DLD and Ht-29 human colon cancer cell lines

Abstract: Summary This study provides new information on the cellular effects of 1,3,5-triazine nitrogen mustards with different peptide groups in DLD and Ht-29 human colon cancer cell lines. A novel series of 2,4,6-trisubstituted 1,3,5-triazine derivatives bearing 2-chloroethyl and oligopeptide moieties was designed and synthesized. The most cytotoxic derivative was triazine with an Ala-Ala-OMe substituent on the ring (compound 7b). This compound induced time- and dose-dependent cytotoxicity in the DLD-1 and HT-29 colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Preliminary work support its versatility in the synthesis of pharmaceutically active compounds. [14][15][16] While other potential applications include use as new chiral auxiliaries 17 building blocks, and pesticides 18 etc.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary work support its versatility in the synthesis of pharmaceutically active compounds. [14][15][16] While other potential applications include use as new chiral auxiliaries 17 building blocks, and pesticides 18 etc.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 30 (Figure 9) obtained via the click chemistry method showed higher potency than doxorubicin. Derivative 30 exhibited an IC50 against MCF-7 and HepG2 cells of 2.95 µg/mL and 3.70 µg/mL, respectively, and showed no toxic activity against the growth of normal HFB4 cells [33].…”
Section: Primary Anticancer Studiesmentioning
confidence: 99%
“…5-fluorouracil exhibited lower activity as a reference. Compound 58 increased the expression of BAX and decreased the amount of Bcl-2 both in DLD-1 and in HT-29 [33]. Screening studies of 2-(dichloromethyl)pyrazolo[1,5-a][1,3,5]triazines 62-66 (Figure 13) showed potential anticancer properties against non-small cell lung cancers, colon cancers, renal cancer, etc.…”
Section: Primary Anticancer Studiesmentioning
confidence: 99%
“…Further appending of hybrid triazine‐nitrogen mustards with amino acids and peptides generated highly potent anticancer hybrids 38 a‐o, 39, 40 and 41 ; Figure 8. These hybrids induced dose‐ and time‐dependent cytotoxicity in the cell lines MCF‐7, DLD‐1, MDA‐MB‐231, and HT‐29 and trigger apoptosis by weakening of intracellular signaling pathways (Fraczyk et al, 2016; Wrobel et al, 2019).…”
Section: Anticancer Properties Of Hybrid Molecules Based On 135‐trimentioning
confidence: 99%